POLICY EVALUATION OF THE EFFECTIVENESS, EFFICIENCY, AND RESPONSIVENESS OF CHILD PROTECTION - Febrina Larasati; R Sally Marisa Sihombing (Jurnal Kebijakan Publik, 2025)
This study aims to evaluate the effectiveness, efficiency and responsiveness of Qanun No. 11/2008 on Child Protection in Central Aceh District. This Qanun was created to provide comprehensive protection for children from various forms of violence and exploitation. However, data shows that cases of violence against children are still high, so an in-depth evaluation of this policy is needed. This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and analysis of related documents. Informants consisted of government officials, professionals, and communities directly involved in the implementation of child protection policies. The policy analysis in the study used Thomas R. Dye's policy evaluation model which includes four main indicators, namely effectiveness, efficiency, responsiveness, and equality. The results show that the implementation of the Qanun still faces various obstacles. From the effectiveness aspect, the policy has not fully reduced the number of violence against children due to weak socialization and law enforcement. From the efficiency aspect, the limited budget and number of professionals are the main obstacles in optimizing child protection services. In terms of responsiveness, delays in handling case reports still occur due to suboptimal coordination between agencies and the lack of digital-based reporting mechanisms.